Analysis of candidate genes within the 3p14-p22 region of the human genome for association with bone mineral density phenotypes - Mullin, Benjamin H (Curtin University, 2011)
Previous studies have identified the 3p14-p22 chromosomal region as a quantitative trait locus for bone mineral density (BMD). The overall aim of this thesis is to identify the gene or genes from this region that are responsible for the linkage observed. The studies described within are centred on the analysis of polymorphisms within candidate genes from 3p14-p22 for association with BMD phenotypes in Caucasian women. Some functional work has also been performed to provide information on the role of these genes in bone cells. It is hoped that by identifying the genes that regulate BMD, a better understanding of osteoporosis may be gained, more effective treatments can be developed and individuals at increased risk of developing the disease can be identified.Osteoporosis is a systemic bone disease characterised by low bone density and micro-architectural deterioration which results in fragile bones that are at increased risk of low-trauma fracture. Peak bone mass is attained in early adult life, but declines in postmenopausal women, in particular, due to a reduction in oestrogen production with effects on bone as well as intestinal and renal calcium handling. However, in addition to the effects of oestrogen, calcium and other environmental factors on bone structure and fracture, there is a strong genetic effect on peak bone mass, bone loss and fracture rates in postmenopausal women. Twin and family studies have suggested that 50 – 90 % of the variance in peak bone mass is heritable. Multiple genetic linkage studies have identified the 3p14-p22 region of the human genome as a quantitative trait locus for BMD. Therefore, it was hypothesised that one or more genes in this genomic region are significantly associated with BMD in Caucasian women.Based on a review of the literature, the ARHGEF3 gene was identified as a positional candidate in this chromosomal region. Common genetic variation within this gene was analysed by genotyping tagging single nucleotide polymorphisms (SNPs) in two populations of Caucasian women using the Illumina GoldenGate assay and matrixassisted laser desorption/ionisation time-of-flight (MALDI-ToF) mass spectrometry techniques, the latter of which was performed in-house. Multiple associations were identified between polymorphism within the ARHGEF3 gene and BMD, with the strongest associations observed between the SNP rs7646054 and various BMD phenotypes in both populations (P < 0.001 – 0.038). This SNP was also found to be significantly associated with fragility fracture rate (P = 0.026). The SNP rs7646054 was found to be located within the 5’ untranslated region of a recently described transcript variant of ARHGEF3 designated NM_001128616. In silico bioinformatics analysis suggested that polymorphism at rs7646054 affects the folding and stability of NM_001128616.Based on the associations identified between the ARHGEF3 gene and BMD phenotypes and a review of the literature, the RHOA gene was identified as a second positional candidate in the 3p14-p22 chromosomal region. Common variation within this gene was analysed by genotyping tagging SNPs in the same two populations of Caucasian women that were used in the ARHGEF3 study using the same genotyping techniques. Multiple associations were identified between polymorphism within the RHOA gene and BMD, with the strongest associations observed between the SNP rs17595772 and various BMD phenotypes in both populations (P = 0.001 – 0.036). The SNP rs17595772 was found to tag a very large linkage disequilibrium block that spans across several other genes in the region.Mutation within another gene from the 3p14-p22 chromosomal region, FLNB (see below), has been implicated in a variety of human genetic disorders characterised by skeletal malformation. Disruption of the gene in mice also results in severe skeletal abnormalities. A recent publication has identified common sequence variation within this gene as significantly associated with various BMD phenotypes and has also identified five SNPs from the 5’ region of the gene as associated with FLNB mRNA expression. These five SNPs were genotyped in a population of Caucasian women using the TaqMan technique. Significant associations were observed between the three SNPs rs11720285, rs11130605 and rs9809315 and various BMD phenotypes (P = 0.004 – 0.043).Subsequent to the aforementioned studies, functional studies were performed to examine the role of the ARHGEF3 and RHOA genes in bone cells. Expression of the ARHGEF3 and RHOA genes was identified in both osteoblast-like and osteoclastlike cells, however expression of the ARHGEF3 transcript variant NM_001128616 was identified in the osteoclast-like cells only. The effect of ARHGEF3 and RHOA gene knockdown in human osteoblast-like and osteoclast-like cells was then investigated to give clues as to the role of these genes in bone cells. Knockdown of RHOA in the Saos-2, hFOB 1.19 and MG-63 osteoblast-like cell lines was consistently found to significantly reduce the expression of alpha 2 actin, smooth muscle (ACTA2) mRNA (P < 0.001), indicating a possible role for RHOA signalling in regulation of ACTA2 gene expression. Knockdown of ARHGEF3 in the Saos-2 osteoblast-like cell line was found to significantly reduce the expression of osteoprotegerin mRNA (P < 0.001 – 0.02), an effect that was replicated in the hFOB 1.19 osteoblast-like cell line (P = 0.003). Knockdown of RHOA in the Saos-2 osteoblast-like cell line was found to significantly increase the expression of parathyroid hormone 1 receptor mRNA (P = 0.002).The protein products of these mRNA transcripts are both involved with the mechanism by which parathyroid hormone stimulates the osteoblast to promote osteoclastogenesis, suggesting a role for the ARHGEF3 and RHOA genes in this process. Knockdown of the ARHGEF3 and RHOA genes in the osteoclast-like cells proved more difficult. However, there was some evidence to suggest that knockdown of RHOA significantly reduces the expression of Rho GDP dissociation inhibitor alpha (P < 0.001 – 0.004) and ACTA2 mRNA (P < 0.001 – 0.003). The effect of ARHGEF3 and RHOA gene knockdown on the bone resorbing capabilities of osteoclast-like cells was then examined. Gene knockdown was performed on osteoclast-like cells cultured on bovine bone slices, with the mean resorption pit volume subsequently calculated for each treatment group. No significant differences were observed between either of the ARHGEF3 or RHOA knockdown groups and the negative control group (P = 0.47 and 0.33 respectively).These studies have identified common variation within the ARHGEF3 and RHOA genes as significantly associated with BMD in Caucasian women. Variation within these genes has not been previously implicated in BMD regulation or osteoporosis. These studies have also provided supporting evidence for association between variation in the FLNB gene and BMD in Caucasian women. All three of these genes are involved with cytoskeletal reorganisation and actin polymerisation, mechanisms that have been shown to have a role in osteoblast differentiation and osteoclast function. This suggests a role for genetic regulation of the cell cytoskeleton as a key pathway in osteoporosis susceptibility. In addition to this, the functional studies performed have highlighted some potential roles for the ARHGEF3 and RHOA genes in bone cells and have provided some leads for future study. Knockdown of these genes in osteoclast-like cells was not found to influence their bone resorptive capabilities, however this could be due to insufficient gene knockdown.